Real options in the assessment of the company’s pro-ecological investments - Dziawgo, Ewa (Copernican Journal of Finance & Accounting, 2014)
The article presents the following issues related to real options: characteristics and classification of options, pricing models and analysis of the applicability of real options in the assessment of the company’s pro-ecological investments. The concept of real options analysis is an innovative mainstream methodology of creating a multi- stage decision-making model to facilitate the action related to the strategic implementation of investment activities. The real options analysis method is alternative and complement to traditional methods of evaluation of investment projects. The purpose of this article is to present the applicability of real options in the assessment of the company’s pro-ecological investments.